Association Between Posyandu Attendance Frequency and Accuracy of Anthropometric Measurement with Stunting Status in Under-Five Children at Puskesmas X - Nada, Alivi Qotrun; Maulidy, Arnetha Arlyn; Herdiani, Novera; Aan Adriansyah, Agus (Jurnal Kesmas Jambi, 2025)
Stunting remains a major public health problem in Indonesia, negatively affecting child development and the quality of human resources. Early detection through routine monitoring at Posyandu (Pos Pelayanan Terpadu) is crucial for stunting prevention. However, low attendance among under-five children and inaccurate anthropometric measurement by cadres often hinder timely interventions. This study aimed to analyze the association between Posyandu attendance frequency and the accuracy of anthropometric measurement with stunting status among under-five children aged 0–59 months at Puskesmas X. A cross-sectional analytical study involving 100 children selected through multistage cluster sampling was conducted. Primary data were obtained through re-measurement using calibrated anthropometric tools, while secondary data were collected from Posyandu attendance records, KIA books, and cadre measurement recaps. Data were analyzed using the Chi-square test with a significance level of p<0.05. The results showed a significant association between Posyandu attendance frequency and stunting status (p = 0.000; OR = 44.33) and between anthropometric measurement accuracy and stunting status (p = 0.017; OR = 0.26). The study concludes that both variables are associated with stunting status among under-five children. Strengthening Posyandu attendance and improving cadre training in accurate anthropometric measurement may enhance early detection and prevention of stunting.